Protective and therapeutic efficacy of mangosteen extract feed additive against Vibrio parahaemolyticus AHPND strain in Pacific white shrimp (Litopenaeus vannamei) - Saengthamat, Warawan; Thawonsuwanb, Jumroensri; Sinprasertporn, Ammara; Khattiya, Rutch; Rojtinnakorn, Jiraporn (Agriculture and Natural Resources, 2025)
Importance of the work: Shrimp aquaculture has faced severe losses due to an epizootic bacterial disease caused by the Vibrio parahaemolyticus AHPND (VpAHPND) strain, characterized by pale-to-white color with atrophy of the hepatopancreas and migh mortality. This study highlights the potential of MEX1TM, a phytobiotic from mangosteen pericarp extract, as a natural, prophylactic feed additive to enhance health and AHPND resistance in Pacific white shrimp. Objectives: To assess the effect of 0.05% (weight per weight) MEX1TM supplement on growth, immune response and resistance to VpAHPND. Materials and Methods: Juvenile shrimp were fed a MEX1TM-supplemented diet and performance was evaluated through growth indices, hematological profiles, enzyme activities and immersion-based AHPND challenge trials mimicking natural infection. Results: MEX1TM significantly improved growth performance (% weight gain, Fulton’s condition factor, average daily gain, specific growth rate, % feed efficiency and feed conversion ratio) and survival rate, which increased from 58.30% in controls to 91.42% in the MEX1™-treated group. The extract enhanced protein digestive enzymes (trypsin and chymotrypsin) and hematological parameters (total hemocyte count, differential hemocyte count and superoxide dismutase). In the VpAHPND resistance test, of the three experimental groups evaluated: controls, Tre-MEX (as the VpAHPND-treated group and Pre-MEX (as the VpAHPND-protected group), the Pre-MEX group had significantly elevated cellular immune parameters and the lowest pathogen loads in the hemolymph, hepatopancreas and intestine compared to both the Tre-MEX and control groups. Main finding: VpAHPND primarily targeted and damaged hyalinocytes, while MEX1TM stimulated hematopoiesis, particularly granulocyte production, in response to infection. The mangosteen extract functioned as a growth promoter and an immunostimulant, boosting shrimp resilience against VpAHPND. These results supported the application of MEX1TM as a natural, effective feed additive for disease prevention and performance enhancement in shrimp aquaculture.